Public’s Perception of the Implementation of Shari’a in Aceh (A Phenomenological Study on the Implementation of Islamic Shari’a in the City of Band Aceh) - Ismail, Fauzi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The implementation of Islamic shari’a in Aceh has been ongoing for about 22 years. This study aims at critically analyzing people's perceptions towards the implementation of Islamic shari'a and the life of the people of Banda Aceh city related to the implementation of Islamic shari'a in a kaffah manner. This research used a qualitative method from a phenomenological perspectives through a grounded research approach. Data collection techniques was done through direct observation, in-depth interviews, and documentation. The data analysis is done through open, axial, and selective coding. The results show that the public’s perception towards the implementation of Islamic shari’a in Banda Aceh city has not been implemented in people's life by qanun No. 11 of 2002 concerning creed, worship, and syi'ar (lecturing). The application of Islamic shari'a is not by the principles and the objectives of it; the direction of its application tends to be political and symbolic. It is only limited to physical matters and not comprehensive in the life of the community, while the substance of it has not been realized in people's life. The life of the people in Banda Aceh city is not much different and no significant changes in people's attitudes before and after the implementation of it.——————————————————————————————————————————————————–Penerapan syari’at Islam di Aceh telah berlangsung selama lebih kurang 22 tahun. Penelitian ini bertujuan untuk menganalisis secara kritis persepsi masyarakat terhadap penerapan syahri’at Islam dan kehidupan masyarakat kota Banda Aceh terkait penerapan syari’at Islam secara kaffah. Penelitian ini menggunakan metode kualitatif dari sudut pandang fenomenologis melalui pendekatan grounded research. Teknik pengumpulan data melalui observasi langsung, wawancara mendalam dan dokumentasi. Analisis data melalui pengkodean terbuka, aksial dan selektif. Hasil penelitian menunjukkan bahwa persepsi masyarakat terhadap penerapan syari’at Islam di kota Banda Aceh belum terimplementasi dalam kehidupan masyarakat berdasarkan qanun Nomor 11 Tahun 2002 tentang Akidah, Ibadah dan Syi’ar. Penerapan syari’at Islam belum sesuai dengan prinsip dan tujuannya; arah penerapannya cendrung politis dan simbolik. Hanya sebatas pada hal- hal yang bersifat fisik dan belum menyeluruh dalam kehidupan masyarakat, sedangkan substansinya belum juga terwujud dalam kehidupan yang nyata dalam masyarakat. Kehidupan masyarakat di Kota Banda Aceh tidak jauh berbeda dan tidak terjadi perubahan sikap masyarakat yang siknifikan sebelum dan sesudah penerapan syari’at Islam.